TEACHING PROCEDURE TEXT IN ENGLISH BASED ON LOCAL CULTURE CONTEXT AT SMAN 1 WONOSARI, BOALEMO - Kartin Lihawa (Journal of Community Services on Multidisciplinary Sciences, 2026)
The purpose of this community service activity is to address common problems faced by high school students, particularly those at SMAN 1 Wonosari, namely their limited English-speaking ability. This problem arises from the lack of daily English communication and insufficient mastery of essential vocabulary. Overcoming this issue, the program aims to improve students’ speaking skills through classroom learning uses “Procedure Texts” as teaching material, contextualized within the students’ local cultural environment. This approach stimulates students’ thinking, facilitates idea expression, and builds confidence in speaking English. Moreover, it is expected to encourage peer influence and community engagement. The activity began with consultations with the school principal and class teachers, followed by the selection of suitable materials. Eclectic, Direct, and Indirect methods were applied, emphasizing individual speaking tasks using culturally relevant topics. A speaking assessment rubric was used to evaluate progress. Among 32 tenth-grade students, initial evaluation showed 26 received D category due to limited vocabulary and low fluency. After implementation, results improved significantly: 3 students achieved A, 16 obtained B, and 13 reached C categories. Comparing those two resutls of students’ speaking evaluation shows us that appying teaching material based on cultural context resulted high students’ ability in English speaking skills.